Food safety management: preventive strategies and control of pathogenic microorganisms in food - Pedro Henrique Mainardi; Ederio Dino Bidoia (European Journal of Biological Research, 2024)
Food security is a paramount concern worldwide, as the consumption of food contaminated by pathogenic microorganisms can result in serious risks to human health. The presence of bacteria, fungi, and other potentially harmful microorganisms in food is a reality that demands rigorous preventive and control measures to ensure the quality and safety of food products. In this context, this review addresses food safety management as a preventive and control measure for pathogenic microorganisms in food, aiming to safeguard public health and ensure product quality. The article discusses the importance of strict hygienic practices throughout the food chain, from production to consumption, and analyzes predominant pathogenic microorganisms that can cause foodborne illnesses. The study highlights the relevance of conventional and advanced techniques for microbiological identification as effective tools for accurate and rapid detection of microorganisms in food. Key elements such as temperature, pH, water activity, and additives are emphasized as crucial in inhibiting microbial proliferation. The implementation of quality management systems, notably the Hazard Analysis and Critical Control Points (HACCP) system, and collaboration among various stakeholders are identified as essential to ensuring food safety. The importance of consumer education regarding safe food handling and storage practices is also emphasized. The conclusion emphasizes the central significance of food safety management as a foundation for population health and well-being, reinforcing that synergy and shared responsibility are indispensable pillars to ensure the supply of safe and healthy food for human consumption.